PENERAPAN MODEL INTERAKSI SOSIAL DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KERJA SAMA SISWA SEKOLAH DASAR - Ananda Nurtasya (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to describe the classroom meeting model pattern as a strategy for strengthening character values in thematic learning at the elementary school level. The background of this research is based on the importance of character education in shaping students’ attitudes and behavior from an early age. This study employs a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of the classroom meeting model is able to enhance students’ character values, such as discipline, responsibility, cooperation, honesty, and mutual respect. Classroom meetings are conducted through discussions, joint reflection, and the habituation of positive behaviors involving active student participation. In addition, the teacher’s role as a facilitator is crucial in guiding the activities to ensure they run effectively and conducive. In conclusion, the classroom meeting model can be an effective strategy for integrating character education into thematic learning in elementary schools.